Embedded Linux based agricultural field monitoring and automation using IoT - L V S Aditya, Bhrugumalla; Subrahmanyam, K (International Journal of Engineering and Technology, 2018)
The main idea of this venture is to have an irrigation system which is self-controlled .it is also observed that the setup is available for a low price. Wi-Fi technology is used to design this setup. It also aims to reduce manual operation in the agricultural field. The changes taking place are noted. The results obtained are further used to develop the field. As the whole setup is online the readings and values are obtained in real-time a Liquid crystal display is used to know the readings of the conditions.Â Â